Effects of access to a well-resourced environment on dairy calf cognition and affective state - Malina Suchon; Daniel M. Weary; Marina A. G. von Keyserlingk (PLoS ONE, 2025)
Dairy calves are often raised without maternal contact and in environments of low complexity. Environments that limit natural behaviors are known to impair cognitive development and affective states. We explored the effect of environmental complexity on one measure of social cognition (the ability to discriminate between conspecifics) and one measure of affective states (sensitivity to reward). Pairs of calves were randomly allocated to either 1) pair housing for 22.5 h/d with 1.5 h of daily access to a well-resourced pen which included 3 other calves and physical devices (Enriched; n = 6 pairs) or, 2) pair housing for 24 h/d (Control; n = 6 pairs). Calves were trained to discriminate between 2 calves in a Y-maze. Twelve of the 24 calves tested met the learning criterion, requiring 15.7 ± 2.59 (mean ± SD) training sessions. Treatment did not affect the number of sessions needed to reach the learning criterion. Calves were then subjected to a Successive Negative Contrast test during which they were trained to approach a 0.5 L milk reward over 3 trials/day for 3 days. On the last training day, latencies of enriched calves increased over daily trials while latencies for control calves were lower and remained relatively consistent, indicative of greater sensitivity to reward. Starting on day 4, the reward was reduced to 0.1L of milk/trial and remained at this level for the next 5 test days. Latency to reach the reward increased across trials within each test day, but no effect of treatment or test day was found. Our findings suggest that calves can discriminate among individuals but learning was not affected by treatments. Calves raised in standard pair housing showed increased sensitivity to reward, consistent with experiencing a more negative emotional state in comparison to calves reared with access to a well-resourced environment.